Preliminary Economic Potential Evaluation of Seaweed Gracilaria sp. Biomass Waste as Bioindustry Feedstock Through a Biorefinery Approach: A Case Study in Karawang, Indonesia - Muhammad Fadhlullah; Sukma Budi Prasetyati; Imam Pudoli; Calvin Lo (School of Life Sciences and Technology, Institut Teknologi Bandung, 2022)
Seaweed processing usually produces biomass waste from unused and rejected materials, which have economic potential due to their bioactive components. This preliminary study aims to evaluate the economic potential of seaweed biomass waste through a biorefinery approach. Seaweed Gracilaria sp. biomass waste samples were collected from a representative seaweed production unit in Karawang, Indonesia, and their biochemical composition was analyzed. Relevant information related to seaweed biomass waste was gathered. The preliminary economic evaluation was assessed from the gross revenue of the proposed products, based on the assumed annual seaweed biomass waste productivity, biochemical composition, and estimated market price of the products. The present study revealed that the dry weight of Gracilaria sp. biomass waste contains 63.2% carbohydrates, 13.6% proteins, 1.6% lipids, and 21.5% ashes. Heavy metals were detected in the biomass waste, although no pigments were detected. This study estimates that 52 metric tons/year of Gracilaria sp. biomass waste could generate amino acids, fatty acids, lipids, carbohydrates, and minerals with potential gross revenue of ± USD 222,924.6/year. This study suggests that Gracilaria sp. biomass waste could be potentially used as feedstock to improve its economic value for bioindustry purposes.